Polymer microsphere inks for semi-solid extrusion 3D printing at ambient conditions - Pohjola, Juuso; Jokinen, Mika; Soukka, Tero; Stolt, Mikael (Elsevier BV, 2026)
Extrusion-based 3D printing methods have great potential for manufacturing of personalized polymer-based drug-releasing systems. However, traditional melt-based extrusion techniques are often unsuitable for processing thermally labile molecules. Consequently, methods that utilize the extrusion of semi-solid inks under mild conditions are frequently employed. The rheological properties of the semi-solid inks have a substantial impact on the 3D printability, making it necessary to evaluate and tailor these properties. Here, we report a novel semi-solid extrusion 3D printing method based on utilization of a Carbopol gel matrix containing various concentrations of polymeric microspheres. We also demonstrate the use of a solvent vapor-based post-processing method for enhancing the mechanical strength of the printed objects. As our approach enables room-temperature processing of polymers typically used in the pharmaceutical industry, it may also facilitate the broader application of 3D printing and microsphere technologies in preparation of personalized medicine.